16S V4-V4 taxonomy classifier ... - Anderson, Sean; Silliman, Katherine; Thompson, Luke (Zenodo, 2023)
16S metabarcoding databases and naive-bayes classifier specific to the V4-V5 region. Built from the Silva 138.1 SSU Ref NR 99 database using Qiime2 (version 2021.2). Primers used: EMP 16S 515f: GTGYCAGCMGCCGCGGTAA EMP 16S 926r: CCGYCAATTYMTTTRAGTTT File description File Description silva-138-99-seqs.qza Full length Silva 138.1 SSU 99 sequences silva-138-99-tax.qza Taxa for full length Silva 138.1 SSU 99 database refseqs_V4-V5.qza Sequences for 16S V4-V5 (primers 515f, 926r), extracted from Silva 138.1 SSU 99, generated by qiime2-2021.2 (forward compatible) classifier_V4-V5.qza Unweighted (uniform) naive-bayes classifier for 16S V4-V5 (primers 515f, 926r) extracted from Silva 138.1 SSU 99, generated by qiime2-2021.2 ... : "This work was supported by award 21392 to the Northern Gulf Institute from NOAA/OAR Ocean Acidification Program." ...